DRUG POISONING: INTEGRATIVE REVIEW (REMUNOM, 2024)
Introduction: Poisoning caused by drugs is one of the main problems studied in public health. Objective: To review through the literature the main intoxications caused by drugs and their main effects on the body. Methodology: Consists of an integrative review. Articles of scientific production between 2015 and 2022 obtained from platforms: Scielo, LILACS and PubMED were selected. Descriptors in Health Sciences (DeCS) were used: Drug intoxication, Treatment, Deaths, Drugs. Results: 96 articles were cataloged and after exclusion and inclusion criteria, only 13 articles were used for discussion. Discussion: Drug intoxications are responsible for causing various damages to health. Of the 13 articles selected, two address lipophilicity as a therapy for the treatment of intoxication, seven address intoxication in a hospital environment, and four address intoxication in a generalized manner associated with medication. Conclusion: Self-medication is one of the main causes of intoxication.